Community Empowerment Through the Diversification of Rosella Products into Fermented Kombucha - Ni Made Ayu Suardani Singapurwa; Aida Firdaus Muhammad Nurul Azmi; A A Made Semariyani; Luh Suriati; I Wayan Sudiarta; Ni Luh Putu Putri Setianingsih; Anak Agung Sagung Manik Chindrawati; Ni Made Defy Janurianti (Unram Journal of Community Service, 2026)
This community service program aimed to enhance the added value of roselle (Hibiscus sabdariffa L.) through the development of kombucha as a functional beverage while empowering the GAPOKWATAN Lumbung Rasa women farmers’ group in Pitra Village, Bali. Prior to the intervention, roselle utilization was limited to dried tea production with low economic value, constrained by limited knowledge, technology, and market access. The program introduced appropriate postharvest technologies, including training in Good Manufacturing Practices (GMP) and Sanitation Standard Operating Procedures (SSOP), fermentation using Symbiotic Culture of Bacteria and Yeast (SCOBY), and product packaging and labeling. Members were also supported with fermentation and packaging equipment to standardize production. Pre- and post-program assessments revealed substantial improvements: hygienic processing increased from 30% to 80%, fermentation skills from 20% to 75%, packaging quality from 25% to 70%, technology adoption from 15% to 85%, and product diversification from 10% to 65%. Beyond technical capacity, the program fostered social empowerment, as women transitioned from supplementary laborers to key innovators and decision-makers in production and marketing. Economically, the group achieved routine production of 10–15 liters of kombucha per week, with an average selling price of IDR 20,000–25,000 per 250 ml bottle, resulting in a 40–50% increase in income compared to previous activities. Environmentally, the process is considered sustainable, as it relies on locally available raw materials without generating hazardous waste. Overall, this initiative demonstrates that roselle kombucha innovation can strengthen community empowerment, gender inclusivity, and local economic sustainability while contributing to functional food development.